Histone deacetylase isoforms regulate innate immune responses by deacetylating mitogen‐activated protein kinase phosphatase‐1. Issue 4 (27th December 2013) - Jeong, Youngtae; Du, Ronghui; Zhu, Xiaolei; Yin, Shasha; Wang, Jian; Cui, Hengmi; Cao, Wangsen; Lowenstein, Charles J.
Abstract : HDAC1, 2, and 3 isoforms regulate innate immune responses by deacetylating MKP‐1, and are potential therapeutic targets in inflammatory diseases. Abstract : The MAPK pathway mediates TLR signaling during innate immune responses. We discovered previously that MKP‐1 is acetylated, enhancing its interaction with its MAPK substrates and deactivating TLR signaling. As HDACs modulate inflammation by deacetylating histone and nonhistone proteins, we hypothesized that HDACs may regulate LPS‐induced inflammation by deacetylating MKP‐1. We found that mouse macrophages expressed a subset of HDAC isoforms (HDAC1, HDAC2, and HDAC3), which all interacted with MKP‐1. Genetic silencing or pharmacologic inhibition of HDAC1, −2, and −3 increased MKP‐1 acetylation in cells. Furthermore, knockdown or pharmacologic inhibition of HDAC1, −2, and −3 decreased LPS‐induced phosphorylation of the MAPK member p38. Also, pharmacologic inhibition of HDAC did not decrease MAPK signaling in MKP‐1 null cells. Finally, inhibition of HDAC1, −2, and −3 decreased LPS‐induced expression of TNF‐α, IL‐1β, iNOS (NOS2), and nitrite synthesis. Taken together, our results show that HDAC1, −2, and −3 deacetylate MKP‐1 and that this post‐translational modification increases MAPK signaling and innate immune signaling. Thus, HDAC1, −2, and −3 isoforms are potential therapeutic targets in inflammatory diseases.